The Effect of Individual Characteristics and Ability, Work Environment and Motivation, and Leadership Style on Employee Performance Construction Projects - Salsabilla Aliza Putri Pambudi; Christiono Utomo (Institut Teknologi Sepuluh Nopember (ITS), 2023)
Companies often encounter several problems, one of which is the uncertainty in market conditions that can lead to company failure. All actions taken in each activity are initiated and determined by humans who are members of the company. Employee performance is one of the most dominant factors in improving company performance which many factors can influence. The effect produced by each factor will certainly be different for each individual. Therefore, this study was conducted to determine how much influence several variables have on employee performance. The population in this study were employees who had or are currently working on a BUMN construction project with a sample of 122 respondents. To test the established hypothesis, this study will use the Structural Equation Modeling (SEM) method with a software program to input data from the questionnaire results, and then it will be calculated to see how fit the proposed model is. There is one relationship path that has no significant effect, namely the relationship between work environment variables and work motivation variables.